The effect of the COVID-19 pandemic on KPS student enrollment and NWEA test scores - Randall W. Eberts (W.E. Upjohn Institute for Employment Research, 2023)
This report focuses on the COVID-19 pandemic in the Kalamazoo Public Schools District in Kalamazoo, Michigan, which closed its doors to students from mid-March 2020 to June 2021. During this time, instruction transitioned from face-to-face to virtual, with students having three options for virtual instruction. In addition to individual KPS student data, the study looks at the NWEA national sample as presented in several publications and technical appendices. The study addresses three basic questions, as well as examining students' race/ethnicity and poverty status, summer learning loss to determine the change in achievement gains, and attendance rates as an example of students not receiving face-to-face instruction. The first question asks whether the pandemic, which began in March of 2020, adversely affected student enrollment. The second question examines how achievement gains based on the NWEA math tests during the 2020-2021 pandemic school year compared to prepandemic and post-school-closure trends. The third question examines the variability of NWEA math test scores during the pandemic compared to the school years before and after the 2020-2021 pandemic school year. We find that student enrollment declined during and after the pandemic school year for at least two years, which is more than appears to be the case in all but the first few years of the century. In addressing the second question, we found that achievement gains rebounded after KPS schools opened, although achievement gains are not as high as in the prepandemic school year. It also appears that the lower grades were more resilient than the upper grades during this period. Regarding the third question, we found that test scores were more variable at the low end of the distribution than at the high end and that variability increased in the year following school closure.
Keywords: I21; I24; 330; Education; students; NWEA tests; grades 3 through 8; COVID-19 pandemic